Crystal Growth - Glebovsky, Vadim (IntechOpen, 2019)
In this book, a variety of topics related to crystal growth is extensively discussed. The topics encompass the physics of growing single crystals of different functional materials, single-crystalline thin films, and even the features of crystallization of biofats and oils. It is intended to provide information on advancements in technologies for crystal growth to physicists, researches, as well as engineers working with single-crystalline functional materials.